Identification of Apple Varieties Resistant to Fire Blight (Erwinia amylovora) Using Molecular Markers - Gulshariya Kairova; Nurzhan Daulet; Maxim Solomadin; Nurlan Sandybayev; Shynggys Orkara; Vyacheslav Beloussov; Nazym Kerimbek; Dilyara Gritsenko; Zagipa Sapakhova (Horticulturae, 2023)
Fire blight of fruit crops is one of the most dangerous diseases for apple trees and other plants of the Rosaceae family, and in Kazakhstan, it is subject to quarantine. To study the spread of fire blight, a phytopathological evaluation of 59 apple varieties of domestic and foreign breeds was carried out in various regions of the south and southeast of Kazakhstan while also considering climatic conditions. The susceptibility of an apple tree to fire blight is influenced by the climatic conditions prevailing in a particular fruit region of Kazakhstan. Samples were collected from various varieties of apple trees with fire blight symptoms for molecular genetic analysis. The phytopathological evaluation and results of the PCR analysis made it possible to identify the causative agent of the disease and its spread to apple varieties in the main fruit regions of Kazakhstan. A molecular study of the resistance to the fire blight pathogen was carried out using the most effective molecular markers. A set of 10 (FBE-1_Y320; FBE-2_Y192; FBE-2_Y495; FBE-2_Y551; FB-MR5-K35; FB-MRS-R240; FB-MR5-R249; FB-MR5-rp16k15_M106; RLP1a; and RLP1b) SNPs was selected, including SNPs reported to be associated with three trait loci, as well as the two markers AE10-375 and GE-8019. Interestingly, the SNP analysis revealed that for all ten markers linked to fire blight resistance, the genotypes of all 59 apple cultivars were identical. No differences in the presence or absence of these markers were observed among the studied varieties. The 26 apple varieties of domestic and foreign breeds most resistant to fire blight were identified in the molecular analysis using the markers AE-375 and GE-8019. Among the studied 59 apple varieties, 23 varieties were identified using the AE-375 marker and 7 varieties with the GE-8019 marker. Samuret, Honeycrisp, Pinova, and Red Topaz were found to be resistant using markers AE-375 and GE-8019. The most promising apple varieties for further breeding for resistance to fire blight programs were selected.